Participatory and Community Development of Sidodadi Village in Pagardewa District, Lampung on Natural Tourism of Fish Park to Improve Economy - Gandes Dwi (Jurnal Al-Hikmah, 2023)
There are many lack of community participation and development in Indonesia. Some of them are: Data from the Ministry of Villages, Disadvantaged Regions, and Transmigration show that many villages in Indonesia have not been involved in government development programs. The focus of this research is: 1) How does community participation and development affect tourism development in Indonesia? 2) What are the benefits of community-based tourism development in improving the well-being of local communities? 3) How was community-based ecotourism development carried out in Tanjung Kalian Village, Lampung? This study employed a qualitative methodology to explore the participatory and community development of Sidodadi Village in Pagardewa District, Lampung. The results of this study are: 1) Lack of community participation and development in tourism is an issue in Indonesia, but community-based tourism development is important for improving local communities' well-being and preserving culture and the environment, 2) The tourist spot in Tanjung Kalian Village, Lampung emphasizes community-based tourism development and prioritizes community well-being. The management involves the community in decision-making and planning and provides humanitarian aid, 3) Community-based tourism development in the fish park in Lampung provides economic benefits for the community, but income is affected by external factors like the pandemic. Sustainable tourism development requires continuous efforts to involve local communities and preserve natural and cultural resources.